Study the association between IL-17 level and autoimmune antibodies in hypo and hyper thyroidisms patients - Fadhil, Marwah F.; Ibraheem, Shaima R.; Al-Kazaz, Abdul Al-Kareem A. (Iraqi Journal of Science, 2019)
The current study included measuring the level of IL-17A and IL-17F and some autoimmune antibodies related to the thyroid gland in case of hypo and hyperthyroid in Iraqi patients to evaluate the correlation between all the measured parameters in this study.The study has been carried out in AL-Kindey Endocrine Gland and Diabetic Center in Baghdad during the period between February 2018 and May 2018, included: 88 patients were divided into three groups, The first group composed of 30 patients of Hypothyroidism that included (26) of them were females, (4) of them males. The second group composed of 30 of patients of Hyperthyroidism that included (20) of them were females, (10) of them were males . and second groups were conducted with hypo and hyperthyroidism respectively.While the third group composed of 28 of healthy individuals (Control) that composed of (25) of them were females, (3) of them were males was represented as control .The results revealed a significant (P < 0.05) correlation between TSH concentration and age in patients groups. When the age is more than 40 years, the concentration of TSH was noticed to be higher than that in patients aged less than 40 years. The results show that the level of antibodies was significantly increased (P<0.01) in hypo and hyperthyroid patients in comparison with the control group. At the same time the level of Anti-TG antibodies was higher significantly in the hypothyroid patients than its level in hyperthyroid patients group. No significant differences have been found between hypo and hyperthyroid patients in the level of Anti-TPO and Anti TSH-R antibodies. But its noticed that the higher level of Anti-TPO Ab. was found in the hypothyroid group where as higher level of Anti TSH-R Ab. was found in the hyperthyroid group and simultaneously both types were significantly higher than their levels in the control group As well as the results demonstrated a highly significant increase (P< 0.01) in the levels of IL-17 Types (A and F) in hypo and hyperthyroid patients with bias toward the comparison with the control group. The statistical study showed a significant negative correlation between the level of TSH and Anti-TG levels (r= -0.33). While a significant positive correlation between the level of Anti-TG and level of IL-17F (r= 0.39) in hypothyroid patients. Also in hypothyroid patients, there is a significant positive correlation between the level of Anti-TPO and IL-17A (r= 0.33). In conclusion: The positive correlation between IL-17F and Anti-TG and between IL-17A and Anti- TPO in hypothyroid patients refer to increase in the concentration of IL-17 may lead to increase the thyroid autoantibodies, which affect thyroid tissue potency, decreasing thyroid hormone production, according to feedback inhibition loop.